Study of self-consumption and net metering photovoltaic system - Serrano-Casares, Francisco Víctor; Mateos, A.; Fernández-Guerrero, J. (My University, 2013)
In Spain, regulations for Self-Consumption installations have been recently approved. However, regulations for Net Metering installations are still under discussion. The target of this study is to discuss different options for Net Metering implementation which are not defined yet. Also, an approach to new criteria for sizing this kind of installations will be done from different points of view: technical and economic. Different cases have been studied: the regulatory frame which was drafted by the former government (but not approved yet) and other proposals amending the mentioned draft that are being issued by other entities as National Energy Commission of Spain, Photovoltaic Producers Association, etc. The results let us conclude that the regulations which are drafted now will not permit the optimal performance of Net Metering installations neither from energy point of view nor economic point of view. It should be necessary to change the regulation draft just to reach the optimal performance of Net Metering installations.
Keywords: Motores térmicos; Self-consumption; Net-metering; Photovoltaic system